Pro C# 2010 and the .NET 4 Platform - Troelsen, Andrew; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
The first edition of this book was released at the 2001 Tech-Ed conference in Atlanta, Georgia. At that time, the .NET platform was still a beta product, and in many ways, so was this book. This is not to say that the early editions of this text did not have merit$1 (Bafter all, the book was a 2002 Jolt Award finalist and it won the 2003 Referenceware Excellence Award. However, over the years that author Andrew Troelsen spent working with the common language runtime (CLR), he gained a much deeper understanding of the .NET platform and the subtleties of the C# programming language, and he feels that this fifth edition of the book is as close to a (3z(Bfinal release(3y (Bas he$1 (Bs come yet. This new edition has been comprehensively revised and rewritten to make it accurately reflect the C# 4 language specification for the .NET 4 platform. You$1 (Bll find new chapters covering the important concepts of dynamic lookups, named and optional arguments, Parallel LINQ (PLINQ), improved COM interop, and variance for generics. If you$1 (Bre checking out this book for the first time, do understand that it's targeted at experienced software professionals and/or graduate students of computer science (so don't expect three chapters on iteration or decision constructs!). The mission of this text is to provide you with a rock-solid foundation in the C# programming language and the core aspects of the .NET platform (assemblies, remoting, Windows Forms, Web Forms, ADO.NET, XML web services, etc.). Once you digest the information presented in these 25 chapters, you$1 (Bll be in a perfect position to apply this knowledge to your specific programming assignments, and you$1 (Bll be well equipped to explore the .NET universe on your own terms.s
Introducing C# and the .NET Platform -- The Philosophy of .NET -- Building C# Applications -- Core C# Programming Constructs -- Core C# Programming Constructs, Part I -- Core C# Programming Constructs, Part II -- Defining Encapsulated Class Types -- Understanding Inheritance and Polymorphism -- Understanding Structured Exception Handling -- Understanding Object Lifetime -- Advanced C# Programming Constructs -- Working with Interfaces -- Understanding Generics -- Delegates, Events, and Lambdas -- Advanced C# Language Features -- LINQ to Objects -- Programming with .NET Assemblies -- Configuring .NET Assemblies -- Type Reflection, Late Binding, and Attribute-Based Programming -- Processes, AppDomains, and Object Contexts -- Understanding CIL and the Role of Dynamic Assemblies -- Dynamic Types and the Dynamic Language Runtime -- Introducing the .NET Base Class Libraries -- Multithreaded and Parallel Programming -- File I/O and Object Serialization -- ADO.NET Part I: The Connected Layer -- ADO.NET Part II: The Disconnected Layer -- ADO.NET Part III: The Entity Framework -- Introducing LINQ to XML -- Introducing Windows Communication Foundation -- Introducing Windows Workflow Foundation 4.0 -- Building Desktop User Interfaces with WPF -- Introducing Windows Presentation Foundation and XAML -- Programming with WPF Controls -- WPF Graphics Rendering Services -- WPF Resources, Animations, and Styles -- WPF Control Templates and UserControls -- Building Web Applications with ASP.NET -- Building ASP.NET Web Pages -- ASP.NET Web Controls, Master Pages and Themes -- ASP.NET State Management Techniques.
Keywords: Computer science; Computer Science; Programming Techniques